2019
DOI: 10.1126/science.aax7890
|View full text |Cite
|
Sign up to set email alerts
|

In vitro culture of cynomolgus monkey embryos beyond early gastrulation

Abstract: Gastrulation is a key event in embryonic development when the germ layers are specified and the basic animal body plan is established. The complexities of primate gastrulation remain a mystery because of the difficulties in accessing primate embryos at this stage. Here, we report the establishment of an in vitro culture (IVC) system that supports the continuous development of cynomolgus monkey blastocysts beyond early gastrulation up to 20 days after fertilization. The IVC embryos highly recapitulated the key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
217
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 169 publications
(235 citation statements)
references
References 41 publications
13
217
0
5
Order By: Relevance
“…Our scRNA-seq data, encompassing 2,475 cells from two independent experiments with multiple gastruloids, uncovered expression of 25,271 transcripts. Comparisons of transcriptomic signatures with mouse (Pijuan-Sala et al, 2019) and cynomolgus monkey (Ma et al, 2019) gastrulae suggest that the hESC gastruloids resemble E7.25 mouse and 14 dpf cynomolgus monkey gastrulae ( Figures 3E-H), and therefore may represent early-to-mid stages of human gastrulation.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Our scRNA-seq data, encompassing 2,475 cells from two independent experiments with multiple gastruloids, uncovered expression of 25,271 transcripts. Comparisons of transcriptomic signatures with mouse (Pijuan-Sala et al, 2019) and cynomolgus monkey (Ma et al, 2019) gastrulae suggest that the hESC gastruloids resemble E7.25 mouse and 14 dpf cynomolgus monkey gastrulae ( Figures 3E-H), and therefore may represent early-to-mid stages of human gastrulation.…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, the ExE-like cluster also expressed amnion marker genes TFAP2A, HAND1, WNT6, and ISL1 (Ma et al, 2019;Zheng et al, 2019) ( Figure 2C). Accordingly, comparison with published datasets suggested that cells in ExE-like cluster resemble both TE and amnion cells.…”
Section: Exe-like Cluster Contains Cells With Gene Expression Profilementioning
confidence: 99%
See 3 more Smart Citations